AN ANALYSIS OF MANUFACTURING MARKET STRUCTURE IN NORTH SUMATRA PROVINCE - Muhammad Asaad; Rasidin Karo-Karo Sitepu (Economic Journal of Emerging Markets, 2011)
This study aims to analyze market structure and manufacturing industry performance on the economy of North Sumatra. The analysis uses two approaches, namely SCP analysis and econometric model. The data used is the Survey of Large Medium 2005-2009. The result shows that the structure of the industry is more dominant, including tight oligopoly, only small parts which belong to loose oligopoly and oligopoly markets. Some industries which have important roles for the economy are the palm oil industry, food and beverage industry, rubber industry and rubber products, and iron and steel basic industries, and basic non-ferrous metals.Keywords: market structure, industry performance, manufacturing industry, local economyJEL classification numbers: L10, L20, L60